Curriculum Management in Encouraging Deep Learning in Vocational High Schools - Kusumawati, Nungky; Hasanah, Enung; santosa, Achadi Budi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Immersive learning is a crucial need in vocational education to address the ever-changing dynamics of the workplace. However, its implementation in Vocational High Schools (SMK) still faces obstacles, particularly related to curriculum management, which tends to be administrative in nature. This study aims to describe in depth the implementation of curriculum management in encouraging deep learning in vocational schools, identifying supporting and inhibiting factors, and revealing school strategies in strengthening learning that aligns with the principles of the Independent Curriculum. This study used a descriptive qualitative approach and was conducted at SMK PGRI 01 Sukorejo, Kendal. Data were collected through semi-structured interviews, participant observation, and documentation studies involving the principal, vice principal for curriculum, teachers, and students. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, conclusion drawing, and verification. The results of the study show that deep learning At SMK PGRI 01 Sukorejo, curriculum management strategies encompass vision-based planning, active and contextual learning, reflective evaluation and supervision, and continuous improvement. These strategies have positively impacted student engagement, increased understanding, critical thinking skills, and readiness to enter the workforce. Despite challenges such as differences in teacher readiness and student abilities, the school has been able to overcome them through a phased approach and a strengthened learning culture. This research underscores the importance of strategic and collaborative curriculum management as a key to success in deep learning in vocational schools.